2015
DOI: 10.1039/c5sm00925a
|View full text |Cite|
|
Sign up to set email alerts
|

Chromatic response of polydiacetylene vesicle induced by the permeation of methotrexate

Abstract: The noble vesicular system of polydiacetylene showed a red shift using two types of detecting systems. One of the systems involves the absorption of target materials from the outer side of the vesicle, and the other system involves the permeation through the vesicular layers from within the vesicle. The chromatic mixed vesicles of N-(2-aminoethyl)pentacosa-10,12-diynamide (AEPCDA) and dimethyldioctadecylammonium chloride (DODAC) were fabricated by sonication, followed by polymerization by UV irradiation. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Therefore, almost reported PDA systems have been conducted in water. Our previous studies on PDAs were also conducted with a vesicle system in water . During the time we designed the PDA studies, we had difficulty because the target compounds were not soluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, almost reported PDA systems have been conducted in water. Our previous studies on PDAs were also conducted with a vesicle system in water . During the time we designed the PDA studies, we had difficulty because the target compounds were not soluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…The weight of one layer was measured using a quartz‐crystal microbalance (QCM) (USI System, Fukuoka, Japan) and quartz resonators (9 MHz) (USI System, Fukuoka, Japan). The N ‐(2‐aminoethyl)pentacosa‐10,12‐diynamide (AEPCDA) was synthesized by using our previously reported method . NMR data: 0.89 (t, 3H), 1.27 (s, 26H), 1.44–1.51 (m, 6H), 2.12 (t, 2H), 2.24 (t, 4H), 2.82 (m, 2H), 3.38 (m, 2H), 4.46 (s, 2H), 6.44 (s, 1H).…”
Section: Methodsmentioning
confidence: 99%
“…The N-(2-aminoethyl)pentacosa-10,12-diynamide (AEPCDA) was synthesized by using our previously reported method. 34…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28] In our research group, diverse PDA sensor systems using several PCDA derivatives have been reported. [29][30][31][32][33][34][35][36] Among them, two color-changeable systems by the permeation of target compound were reported. [33,34] In the first report, [33] a PCDA derivative with an amine group at the end of the compound was synthesized and the sensing system was formed with this compound and dioctadecyldimethylammonium chloride (DODMAC).…”
Section: Introductionmentioning
confidence: 99%